2003
DOI: 10.1084/jem.20022226
|View full text |Cite
|
Sign up to set email alerts
|

Competition Between Two MHC Binding Registers in a Single Peptide Processed from Myelin Basic Protein Influences Tolerance and Susceptibility to Autoimmunity

Abstract: Experimental allergic encephalomyelitis (EAE) is an animal model for multiple sclerosis induced by stimulating myelin basic protein (MBP)-specific T cells. The MBP-specific repertoire in B10.PL mice is shaped by tolerance mechanisms that eliminate MBP121–150–specific T cells. In contrast, MBPAc1–11–specific T cells escape tolerance and constitute the encephalitogenic repertoire. To determine if this differential tolerance is caused by differences in the abundance of MBP epitopes generated by processing, MBP pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 21 publications
(31 reference statements)
1
35
0
Order By: Relevance
“…First, why is the 9 -23 segment of the insulin B chain a central focus of the T cell response? An explanation may lie in the studies from Goverman's laboratory (38) on the response to myelin basic protein. Their data suggest that a different segment of the protein binds with high affinity and the T cells to it are negatively selected.…”
Section: Discussionmentioning
confidence: 99%
“…First, why is the 9 -23 segment of the insulin B chain a central focus of the T cell response? An explanation may lie in the studies from Goverman's laboratory (38) on the response to myelin basic protein. Their data suggest that a different segment of the protein binds with high affinity and the T cells to it are negatively selected.…”
Section: Discussionmentioning
confidence: 99%
“…It remains questionable whether these T cells can be activated with the autoantigen in vivo or whether they rather represent cross-reactive cells specific for different nominal Ags and are mostly unrelated to the autoimmune processes. The emerging animal studies suggest that the latter is true (13,21), and our clinical experience with an altered peptide ligand of MBP [83][84][85][86][87][88][89][90][91][92][93][94][95][96][97][98][99] demonstrated that disease-mediating T cells recognized the native MBP peptide with unexpectedly high functional avidities (22,23).…”
Section: Ultiple Sclerosis (Ms)mentioning
confidence: 99%
“…1B, second panel). However, only several myelin epitopes contributed to the increased reactivity observed in MS patients: MBP epitopes (MBP [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] , MBP 111-129 , and MBP 146 -170 ), PLP 139 -154 , and MOG (MOG [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] and MOG ) (Fig. 1B).…”
Section: Reactivity To a Set Of Myelin Ags In An Il-7-modified Primarmentioning
confidence: 99%
“…Fourier Transform instrumentation also enables estimation of relative abundance of different peptides [24,25], providing an additional dimension of information for use in understanding how the immune system discriminates important antigens. Combined ion-trap and Fourier Transform instrumentation also makes it possible to compare the dominant peptides in two samples, identify differences, and sequence them -a true "differential peptide display" technique [66,85,147]. This approach has been substantially enhanced through the use of stable isotope labeling, enabling the identification of peptides selectively displayed by MHC molecules on cancer and infected cells [148][149][150][151][152].…”
Section: Future Directions and Challengesmentioning
confidence: 99%